Work in the Future - Menasche, Steve; Schnaubelt, Teri (Ascent Audio, 2020)
This short, accessible book seeks to explore the future of work through the views and opinions of a range of expertise, encompassing economic, historical, technological, ethical, and anthropological aspects of the debate. The transition to an automated society brings with it new challenges and a consideration for what has happened in the past; the editors of this book carefully steer the listener through future possibilities and policy outcomes, all the while recognizing that while such a shift to a robotized society will be a gradual process, it is one that requires significant thought and consideration.